2021
DOI: 10.3390/plants10112527
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Molecular Characterization of Some Egyptian Six-Rowed Barley (Hordeum vulgare L.)

Abstract: Barley production is essential in Egypt. In the present study, 15 different six-rowed Egyptian barley cultivars were studied. To differentiate between the different cultivars under study in terms of morphological characteristics and ISSR, molecular characterization reactions were carried out. Moreover, four cultivars (Giza 123, Giza 126, Giza 136, and Giza 138) were selected for further studies using scanning electron microscopy (SEM). Computational analysis of the DNA barcoding sequences of the two plastid ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…In the present study, the recorded amplicons were shorter (approximately 600 and 900 bp for rbcL and matK, respectively), allowing for effective sequencing even though many authors deny the region as a barcode if it is longer than 1000 bp due to difficulties in bi-directional sequencing [87]. Our findings agreed with those of Mohamed et al [94], who concluded that the matK gene is more flexible than the rbcL gene among Egyptian barley (Hordeum vulgare L.) cultivars, and the documented size of the matK region's PCR product was 900 bp, whereas the rbcL region was 600 bp.…”
Section: Dna Barcoding: Plastid Rbcl and Matk Loci Sequencingsupporting
confidence: 91%
“…In the present study, the recorded amplicons were shorter (approximately 600 and 900 bp for rbcL and matK, respectively), allowing for effective sequencing even though many authors deny the region as a barcode if it is longer than 1000 bp due to difficulties in bi-directional sequencing [87]. Our findings agreed with those of Mohamed et al [94], who concluded that the matK gene is more flexible than the rbcL gene among Egyptian barley (Hordeum vulgare L.) cultivars, and the documented size of the matK region's PCR product was 900 bp, whereas the rbcL region was 600 bp.…”
Section: Dna Barcoding: Plastid Rbcl and Matk Loci Sequencingsupporting
confidence: 91%
“…The comparison information of genetic diversity and phenotypic evaluations one of important factors to understand and investigate in germplasm collections or breeding material helps the breeders to plan their programs for specific environments using targeted traits and molecular markers (Mohamed, et al, 2021, Mariey et al, 2022Mariey et al, 2023) They reported that both PCA and heatmap cluster analysis had used successfully in understanding the information of phenotypic evaluations and genetic diversity of the barley genotypes as an important factors using to helps the breeders to but good plan for their programs for specific environments using targeted traits and molecular markers.…”
Section: Association Analysis Of Phenotypic and Genotypic Datamentioning
confidence: 99%
“…The association between molecular markers and phenotypic evaluation remains one of significant aspects to examine the genetic role of tolerance by guess the genomic regions that touch plant's response will be useful as a comprehensive evaluation in breeding programs for environmental stress (Mohamed, et al, 2021;Mariey et al, 2022Mariey et al, & 2023.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the accumulation of sodium ions, which promote the generation of reactive oxygen species (ROS) like the hydroxyl radical, singlet oxygen, hydrogen peroxide, and superoxide, salinity causes osmotic stress and ionic toxicity [ 12 ]. This causes oxidative stress, which damages mitochondria, chloroplasts, the functional structure of cells, biomolecules including lipids, proteins, and nucleic acids, etc., leading to lipid peroxidation, protein denaturation, and DNA mutation in plant cells [ 13 , 14 ]. Therefore, plants can produce antioxidants to scavenge ROS [ 15 ].…”
Section: Introductionmentioning
confidence: 99%